Candi Ratu Boko: Peninggalan Historis Awal Bersatunya Hindu-Budha Masa Jawa Kuno - Titah Pratyaksa, I Gede (PANGKAJA, 2012)
Ratu Boko temple situated in Orchard Dawung Bokoharjo village, Prambanan district, Sleman regency. Originally a magnificent building that was built during the reign of King Rakai Panangkaran, which is one of the descendants Wangsa dynasty in 745-784 AD This temple has Hindu elements. It can be seen from the Linga and Yoni, Ganesha statues, and gold plate that reads